Pencegahan Infeksi dan Transfer Mikroorganisme - Aldona Diva Aurelia; Alma Danita; Echa Ananta Perdani; Evanda Gita Septiana; Rina Fitriani; Via Aulia Ramadani; Liss Dyah Dewi Arini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to synthesize the latest scientific evidence on the main ways microorganisms (bacteria, viruses, fungi) spread and assess the most important infection prevention strategies. This study used a narrative literature review method. Articles were searched in scientific databases such as PubMed, Google Scholar, and Scopus, as well as guidelines from global health organizations such as the WHO and the CDC. Keywords used included "infection prevention," "microorganism transfer," "mode of transmission," "hand hygiene," and "standard precautions." Relevant articles published in the last ten years were then analyzed and summarized. The study found that microorganisms spread through several main routes, such as direct or indirect contact through objects (fomites), droplet droplets, through the air (airborne), through food or water (vehicles), or through vectors. Breaking the chain of infection depends heavily on the implementation of Standard Precautions for all patients. Hand hygiene was identified as the single most important and cost-effective intervention. Proper use of Personal Protective Equipment (PPE), cough etiquette, and environmental cleaning also play a crucial role. In addition, Transmission-Based Precautions are needed for certain pathogens that spread through specific pathways.